Hauntings, homeopathy, and the Hopkinsville Goblins: using pseudoscience to teach scientific thinking - Schmaltz, Rodney; Lilienfeld, Scott O. (My University, 2014)
With access to information ever increasing, it is essential that students acquire the skills to distinguish fact from fiction. By incorporating examples of pseudoscience into lectures, instructors can provide students with the tools needed to understand the difference between scientific and pseudoscientific or paranormal claims. We discuss examples involving psychics, ghosts, aliens, and other phenomena in relation to scientific thinking. In light of research literature demonstrating that presenting and dispelling scientific misconceptions in the classroom is an effective means of countering non-scientific or pseudoscientific beliefs, we provide examples of pseudoscience that can be used to help students acquire healthy skepticism while avoiding cynicism. From Dr. Oz promoting homeopathy to Deepak Chopra extolling the virtues of quantum healing, students are bombarded with questionable claims that require careful examination. Although students have access to more information than ever before, many do not possess the skills to distinguish good information from bad. Exacerbating this problem is the prevalence of pseudoscientific information available in the popular media, online, and even the classroom (Lilienfeld et al., 2004; Losh and Nzekwe, 2011; Novella, 2013). The purpose of this article is to provide examples that challenge students and provide instructors with tools to enhance scientific thinking. To do so, we describe how to distinguish science from pseudoscience, and provide several examples that can be used to promote scientific thinking. Specifically, we want to encourage students to employ scientific skepticism. Scientific skepticism means approaching claims with an open mind, and a willingness to accept only those claims that have survived scrutiny in rigorous scientific tests (Sagan, 1995). Skepticism differs from cynicism, which implies close-mindedness to novel claims. Through unique class demonstrations, assignments, and lecture material, instructors can use pseudoscience as a vehicle to engage students and foster scientific skepticism (see Stanovich, 2012 as a valuable resource). Teaching scientific methods and the nature of science alone is not sufficient to help students distinguish science from pseudoscience. Data from educational psychology suggest that unless misconceptions are addressed explicitly in coursework, they will frequently persist (e.g., Winer et al., 2002). Overcoming students’ naïve scientific beliefs is a significant challenge for educators, as researchers have found that these beliefs can endure even after the acquisition of incompatible scientific theories (Shtulman and Valcarcel, 2012). In a survey of 10,000 American students over a 20-year period, there was only a modest decline in pseudoscientific beliefs following an undergraduate degree, even for students who had taken two or three science courses (Impey et al., 2012). At the same time, there is hope. Researchers have found that short-term skeptical thinking improves among students who have had direct exposure to the refutation of pseudoscientific claims (Kowalski and Taylor, 2009; Manza et al., 2010), although long-term follow-ups are needed to corroborate these findings. Incorporating examples of scientific misconceptions in lectures can be a valuable tool for science educators to help students overcome erroneous scientific beliefs and distinguish science from pseudoscience (see Lilienfeld et al., 2001 for a brief review of the literature).
Keywords: scientific thinking; skepticism; pseudoscience; teaching resources; introductory psychology